Challenges of using modern social media on the institution of the family in The Twenty-first century – Descriptive study - Al Jamil, Yusriya Ali Aman (Journal of Humanities & Social Sciences, 2023)
The researcher conducted this study to identify the main challenges facing the institution of the family in the 21st century with the widespread use of social media platforms by its members. To achieve the objectives of this study, the researcher used an electronically designed questionnaire using Google Drive templates. This questionnaire consisted of 24 statements, distributed across three main axes related to the study questions. It was distributed through different social media platforms to obtain responses from the target audience, which was family members. The sample size reached 238 individuals representing various Arab countries, including Oman, Saudi Arabia, Syria, the Arab Republic of Egypt, and other countries. The study revealed the following results: 1.WhatsApp application ranks highest in terms of daily usage among the sample, with 76.8% of respondents using it. 2. There are numerous challenges that the institution of the family faces due to the use of various social media platforms, including: - 44.5% of the sample believes that these platforms contribute to isolation among family members. - 62.6% of the sample believes that there are morally inappropriate websites that can expose their children to cyberbullying or become victims of fraud and deception. - 39.1% of parents say that these platforms have made it difficult for them to instill values and virtues in their children. The study also resulted in several challenges related to family security and national belonging. In light of the aforementioned, the researcher provided several recommendations, including: 1. Designing a cognitive, advisory, and behavioral program to address the addiction of some family members to these websites. 2. Providing educational courses through social media platforms for family members that serve their common good and society. 3. Introducing educational curricula in the educational system under the title "Digital Education."
Keywords: social media; family; internet; digital education; The Twenty-first century